Quantitative Evaluation of Therapeutic Response by FDG-PET–CT in Metastatic Breast Cancer - Goulon, Dorothée; Necib, Hatem; Henaff, Brice; Rousseau, Caroline; Carlier, Thomas; Kraeber-Bodere, Françoise (Frontiers in Medicine, 2016)
Purpose To assess the therapeutic response for metastatic breast cancer with 18F-FDG PET, this retrospective study aims to compare the performance of 6 different metabolic metrics with PERCIST, PERCIST with optimal thresholds and an image-based parametric approach. Methods Thirty six metastatic breast cancer patients underwent 128 PET scans and 123 lesions were identified. In a per-lesion and per-patient analysis, the performance of 6 metrics: SUVmax (maximum Standardized Uptake Value), SUVpeak, SAM (Standardized Added Metabolic activity), SUVmean, metabolic volume (MV), TLG (total lesion glycolysis) and a parametric approach (SULTAN) were determined and compared to the gold standard (defined by clinical assessment and biological and conventional imaging according RECIST 1.1). The evaluation was performed using PERCIST thresholds (for per-patient analysis only) and optimal thresholds (determined by the Youden criterion from the Receiver Operating Characteristic curves). Results In the per-lesion analysis, 210 pairs of lesion evolutions were studied. Using the optimal thresholds, SUVmax, SUVpeak, SUVmean, SAM and TLG were significantly correlated with the gold standard. SUVmax, SUVpeak and SUVmean reached the best sensitivity (91 %, 88 % and 83% respectively), specificity (93%, 95% and 97% respectively) and negative predictive value (NPV, 90%, 88% and 83% respectively). For the per-patient analysis, 79 pairs of PET were studied. The optimal thresholds compared to the PERCIST threshold did not improve performance for SUVmax, SUVpeak and SUVmean. Only SUVmax, SUVpeak, SUVmean and TLG were correlated with the gold standard. SULTAN also performed equally: 83% sensitivity, 88% specificity and NPV 86%. Conclusions This study showed that SUVmax and SUVpeak were the best parameters for PET evaluation of metastatic breast cancer lesions. Parametric imaging is helpful in evaluating serial studies.